The Impact of Covid-19 amongst International Students in UNIMAS - Florianna Lendai, Michael Mulok; Shanti Faridah, Salleh; Ernisa, Marzuki (UNIMAS Publisher, 2021)
The COVID-19 pandemic has altered the landscape of the education domain. It affects the way we teach, the way we learn, and imposes novel obstacles in the way institutions of higher learning conventionally manage themselves. While all students in higher learning institutions would certainly feel the impact, there is a need to focus on the experience of international students. In an effort to combat the pandemic, Malaysia has issued a directive for Movement Control Order (MCO), starting 18 March 2020. Amongst others, this directive directly affected all universities in the country. This study aims to explore the impact of COVID-19 amongst the international students in a higher education institution in Sarawak, Malaysia. Data was gathered via an online questionnaire adapted from the QS Survey Report 2020 on COVID-19. Our findings revealed that while most of the international students perceived their studies to be affected, most planned to continue with the programs that they were currently enrolled in. The students expressed deep concerns about the impact of the pandemic on their exams and classes and preferred reassurance in terms of updates on information related to academic matters.